Perspektif ASEAN Terhadap Prinsip Non-Intervensi - Widiastuti, Arum (JURNAL USM LAW REVIEW, 2022)
This study aims to examine the implementation of the Non-Intervention Principle for ASEAN member countries. This study uses a normative juridical research method. ASEAN was founded under the Bangkok Declaration on August 8, 1967, with ten members from Southeast Asia still adhering to the principle of Non-Intervention enshrined in the 1976 Treaty of Friendship and Cooperation in Southeast Asia (TAC) and the ASEAN Charter. ASEAN has grown into a large international organization and is starting to be respected by the international community, the principle of Non-Intervention is still a persistent problem in ASEAN, and ASEAN leaders must think about flexibility. This principle is intended to assist a Member State in dealing with problems, particularly those concerning humanity. The results of this study explain that the principle of Non-Intervention that has been maintained so far has greatly contributed to the existence of ASEAN. The application of the principle of Non-Intervention should not be done rigidly so that law enforcement agencies in the field of human rights have a margin of maneuver to formulate recommendations or contributions about what should be a member state.Penelitian ini bertujuan untuk mengkaji pelaksanaan prinsip Non-Intervensi bagi negara-negara anggota ASEAN. Penelitian ini menggunakan metode penelitian yuridis normatif. ASEAN didirikan berdasarkan Deklarasi Bangkok pada   8 Agustus 1967, dengan   sepuluh anggota dari Asia Tenggara masih menganut prinsip Non-Intervensi yang diabadikan dalam Traktat Persahabatan dan Kerjasama di Asia Tenggara (TAC) 1976 dan Piagam ASEAN. ASEAN telah tumbuh menjadi organisasi internasional yang besar dan mulai dihormati oleh masyarakat internasional, prinsip Non-Intervensi masih menjadi masalah yang terus-menerus di ASEAN, dan para pemimpin ASEAN harus memikirkan fleksibilitas. Prinsip ini dimaksudkan untuk membantu suatu negara anggota menghadapi masalah, khususnya yang menyangkut kemanusiaan. Hasil penelitian ini menjelaskan bahwa prinsip Non-Intervensi yang dipertahankan hingga saat ini sangat berkontribusi terhadap eksistensi ASEAN. Penerapan prinsip Non-Intervensi tidak boleh dilakukan secara kaku agar lembaga penegak hukum di bidang hak asasi manusia memiliki margin of manuver untuk merumuskan rekomendasi atau kontribusi tentang apa yang seharusnya menjadi negara anggota.